ANTIBIOTIC RESISTANCE OF Salmonella spp. ISOLATED FROM POULTRY MEAT AND THE ANTIMICROBIAL EFFECT OF PLANTS EXTRACTS - Guzmán, Franco; Velasco, Valeria; Bonilla, Ana María; Williams, Pamela; Medina, Felipe; Gerding, Macarena; Folch, Christian; Oyarzúa, Pía (Chilean Journal of Agricultural & Animal Sciences, 2025)
Salmonella spp. is one of the major pathogens causing foodborne disease outbreaks worldwide. It is a priority public health concern due to antimicrobial resistant strains. Poultry is considered to be a major source of transmission of Salmonella spp. The objective of this study was to determine the prevalence and susceptibility of Salmonella spp. strains isolated from poultry to antibiotics and to oregano essential oil (Origanum vulgare L.), chestnut shell extract (Castanea sativa) and grape pomace extract (Vitis vinifera). Samples were collected from chickens, hens and broilers (cloacal swabs) (n=120), poultry meat (n=98) and eggs (n=138). Salmonella spp. were isolated by selective enrichment and culture method and confirmed by polymerase chain reaction (PCR) (identification of hilA gen). ERIC fingerprinting PCR was used to select strains according to their genetic diversity. Susceptibility of selected strains to antibiotics and plant extracts was determined by disk diffusion method and minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by dilution method. The total prevalence of Salmonella spp. was 6.53% (23/356) and only meat samples were positive, with a higher prevalence in packaged meat (P ? 0.05). All selected strains were multi-drug resistant, i.e. resistant to three or more classes of antibiotics. Oregano essential oil and chestnut shell extract had antibacterial activity against resistant Salmonella spp. isolates. However, grape pomace extract showed no inhibitory activity. Therefore, the use of oregano essential oil and chestnut shell extract at some stages of the poultry production chain should be evaluated in future studies to have solutions for the industry.